The incidence of peripheral arterial embolism in association with a patent foramen ovale (right-to-left shunt) - Ali Kausar Rushdi, Yusuf (Royal Society of Medicine Press, 2011)
OBJECTIVES: The aim of this study was to examine a cohort of patients who had suffered an arterial embolism to see whether a patent foramen ovale (PFO) was an identifiable cause. DESIGN: This study was conducted in two parts; a retrospective limb involving an audit of patient records over a period of 10 years, and a prospective limb including selected patients from that audit to search for a PFO using an agitated saline test with transcranial Doppler ultrasound monitoring of the anterior cerebral artery. Data on patients with peripheral vascular disease were collected using a structured questionnaire. SETTING: A clinical vascular department. All patients were seen in the vascular outpatients clinic. PARTICIPANTS: Patients who had been identified from a retrospective search based on the headline diagnosis of arterial embolus. Collected data on the 71 patients revealed that 75% had predisposing factors for DVT, 70% were male smokers, and 84.4% had a significant past history of vascular symptoms. MAIN OUTCOME MEASURES: Whether or not patients identified as having a possible PFO actually had one on objective testing with transcranial Doppler assessment of the cerebral circulation with an agitated saline solution. RESULTS: Fifteen patients who were suspected of having a PFO were selected from these 71 patients; 12 of these were found to have no PFO on testing, and three had already undergone a percutaneous PFO closure. CONCLUSION: The incidence of a PFO in this small study group is no higher than that found in the general population (3/15, 20%). There was high prevalence of male smokers with associated predisposing factors leading to a DVT.